Circulating microRNAs as candidate markers to distinguish heart failure in breathless patients. (October 2013) - Ellis, Katrina L.; Cameron, Vicky A.; Troughton, Richard W.; Frampton, Chris M.; Ellmers, Leigh J.; Richards, A. Mark
<x xml:space="preserve">Abstract</x> Aims Since their identification in the circulation, microRNAs have received considerable interest as putative biomarkers of cardiovascular disease. We have investigated the diagnostic utility of microRNAs in differentiating between patients with heart failure (HF) and non‐HF‐related breathlessness, and between HF with reduced (HF‐REF) and preserved (HF‐PEF) EF. Methods and results MicroRNA profiling was performed on plasma from 32 HF and 15 COPD patients, as well as 14 healthy controls. Seventeen microRNAs were selected for validation in 44 HF, 32 COPD, 59 other breathless, and 15 controls. Cases of HF were split evenly between HF‐REF and HF‐PEF. Diagnostic utility was compared with NT‐proBNP and high sensitivity troponin T (hs‐troponin T). MiR‐103 [area under the curve (AUC) = 0.642, P = 0.007], miR‐142‐3p (AUC = 0.668, P = 0.002), miR‐199a‐3p (AUC = 0.668, P = 0.002), miR‐23a (AUC = 0.637, P = 0.010), miR‐27b (AUC = 0.642, P = 0.008), miR‐324‐5p (AUC = 0.621, P = 0.023), and miR‐342‐3p (AUC = 0.644, P = 0.007) were associated with HF diagnosis in regression and receiver operating characteristic (ROC) analyses. Individually, NT‐proBNP (AUC = 0.896, P = 9.68 × 10−14) and hs‐troponin T (AUC = 0.750, P = 2.50 × 10−6) exhibited greater sensitivity and specificity. However, combining significantly associated microRNAs with NT‐proBNP improved the AUC of NT‐proBNP by 4.6% (P = 0.013). Four microRNAs, miR‐103, miR‐142‐3p, miR‐30b, and miR‐342‐3p, were differentially expressed between HF and controls, COPD, and other breathless patients (P = 0.002–0.030). Eight microRNAs that distinguished between HF‐REF and HF‐PEF in screening (P = 0.017–0.049) were not replicated in the validation. Conclusions Four microRNAs distinguished between HF and exacerbation of COPD, other causes of dyspnoea, and controls. Seven were associated with HF diagnosis in regression and ROC analysis. Although individually NT‐proBNP was far superior in predicting HF, combining microRNA levels with NT‐proBNP may add diagnostic value.